The investigation as an environmental education strategy - Rojas Bahamón, Magda; Arbeláez-Campillo, Diego Felipe; Prieto, José David (Revista de la Universidad del Zulia, 2019)
This article presents a meaningful experience developed in the Agrotécnico Mixto High School in Caquetá Colombia with the participation of students, teachers and some representatives from the community which aims researching practices about environmental education towards taking care of the Pescado river as a water resource. The methodology used in this case was qualitative with a descriptive - interpretative approach. Several stages were developed: information gathering, systematization and analysis and interpretation of results. One of the most important findings was to find out that researching  as an environmental education strategy can generate attitudinal changes in the students towards taking care and conservation of natural resources.